2017
DOI: 10.5846/stxb201606301342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land-use change on net primary productivity in Beijing based on the MODIS series

Abstract: 第 37 卷第 18 期 2017 年 9 月 生 态 学 报 ACTA ECOLOGICA SINICA Vol.37,No.18 Sep.,2017 http: / / www.ecologica.cn 基金项目:国家自然科学基金重点项目(41530635) ;国家自然科学基金面上(41571173) 收稿日期:2016• 06• 30; 网络出版日期:2017• 04• 25 * 通讯作者 Corresponding author.E•mail: shiliangliu@ bnu.edu.cn DOI: 10.5846 / stxb201606301342 成方妍,刘世梁,张月秋,尹艺洁,侯笑云.基于 MODIS 序列的北京市土地利用变化对净初级生产力的影响.生态学报,2017,37(18) :5924• 5934. Cheng F Y, Liu S L, Zhang Y Q, Yin Y J, Hou X Y.Effects of land•use change on net primary productivity in Beijing based on the MODIS series.Acta Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that landscape pattern is correlated with NPP, and the change in NPP is influenced by the change in landscape pattern [3,4]. In order to understand the influence of landscape pattern on NPP in detail, we determined the scale effect of the correlation between landscape pattern and NPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that landscape pattern is correlated with NPP, and the change in NPP is influenced by the change in landscape pattern [3,4]. In order to understand the influence of landscape pattern on NPP in detail, we determined the scale effect of the correlation between landscape pattern and NPP.…”
Section: Discussionmentioning
confidence: 99%
“…Landscape patterns are closely related to landscape diversity and ecological value [2], which is of great significance for studying the sustainable development of ecosystems. Human activities have a certain degree of influence on landscape patterns, especially when landscape fragmentation and diversity increase [3,4], which can lead to environmental degradation. Analyzing changes in landscape patterns has been proven to help identify some of the impacts between human activities and changes in natural conditions [5], while net primary productivity is also significantly affected by these changes [6].…”
Section: Introductionmentioning
confidence: 99%
“…The shift from carbon sinks to carbon sources was associated with LULCC due to net primary productivity (NPP) reduction in tropical peat lands [17]. LULCC contributed 34% of NPP growth in the period of 2000-2006; however, the change in NPP hindered growth by 27% in the period of 2006-2012 in Beijing, China [18]. The contribution rates of vegetation land-use type area change to NPP change in the periods 2000-2010 and 2010-2020 were 18% and 34%, respectively, in the Beijing-Tianjin-Hebei region of China [11].…”
Section: Introductionmentioning
confidence: 99%